EXPLOSIVE INSTABILITY IN TYPE II SUPERCONDUCTORS - Taylanov, Nizom; Urazov, Abdixoliq (Физико-технологического образование, 2023)
A theoretical study of the development of thermomagnetic instability such as a magnetic flux jump in a type II superconductor located in a flat semi-infinite sample was carried out within the framework of the Wien critical state model. An expression for thermomagnetic instability in the sample is determined